PdCl2 Immobilized in Ionic Liquids: A Novel and Efficient Catalytic System for Michael Additions of Indoles to ,α,β-Unsaturated Ketones - Lin, Xufeng; Cui, Sunliang; Wang, Yanguang (Letters in Organic Chemistry, 2006)
Palladium(II) chloride immobilized in ionic liquid [bmim][BF4] catalyzes the Michael reaction of indoles with α,β-unsaturated ketones to afford the corresponding β-indolylketones in excellent yields. The reaction proceeds at 0.1 mol% of Pd loading with high efficiency and great selectivity. The possible mechanism of the reaction was suggested.
Keywords: ionic liquid